Development and Validation of Instrument for Operative Competency Assessment in Selective Neck Dissection. (February 2023) - Dowling, Eric; Larson, David; Carlson, Matthew L.; Price, Daniel L.
Background: Instruments to assess surgical skills have been validated for several key indicator procedures in otolaryngology. Selective neck dissection is a core procedure for which trainees must integrate knowledge of complex head and neck anatomy with technical surgical skills. An instrument for assessment of surgical performance in selective neck dissection has not been previously developed. The objective of the current study is to develop and validate an instrument for assessing surgical competency for level II-IV selective neck dissection. Design: A Delphi working group comprised of 23 fellowship trained head and neck surgeons from 17 institutions was assembled. The modified Delphi method encompassed a 3-step process, including 2 anonymous voting rounds to successively refine individual items and establish levels of consensus. Thresholds for achieving strong consensus, at >80% agreement, were determined a priori. The resulting instrument was subsequently validated in a prospective cohort of 17 resident surgeons, spanning postgraduate year 1 to 5 training experience. Participants were asked to perform a level II-IV selective neck dissection on fresh-frozen cadaveric specimens. Performance was scored by 2 independent, blinded observers using the devised instrument and construct validity was assessed. Results: Through the modified Delphi process a final list of 30 items, considered to be the most essential items for achieving the goals of a level II-IV selective neck dissection, was developed. Construct validity was supported by a positive association between instrument scores compared to both resident postgraduate year level and number of head and neck rotations completed. Conclusion: The development and validation of a novel instrument for assessment of surgical competency in level II-IV selective neck dissection, a key indicator case in otolaryngology, is described. This new instrument may be used to provide objective feedback on overall and task-specific competency to identify surgical deficiencies and offer granular feedback to enhance surgical training.